2016
DOI: 10.1371/journal.pone.0149099
|View full text |Cite|
|
Sign up to set email alerts
|

CDK1 Is a Synthetic Lethal Target for KRAS Mutant Tumours

Abstract: Activating KRAS mutations are found in approximately 20% of human cancers but no RAS-directed therapies are currently available. Here we describe a novel, robust, KRAS synthetic lethal interaction with the cyclin dependent kinase, CDK1. This was discovered using parallel siRNA screens in KRAS mutant and wild type colorectal isogenic tumour cells and subsequently validated in a genetically diverse panel of 26 colorectal and pancreatic tumour cell models. This established that the KRAS/CDK1 synthetic lethality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 45 publications
1
49
0
Order By: Relevance
“…Therefore, KRAS may affect cell cycle processes. In a recent study, CDK1 is reported as a synthetic lethality target for KRAS mutation in colon cancer [34]. Our study highlisht RAD51AP1 as a prognostic marker and therapeutic target.…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, KRAS may affect cell cycle processes. In a recent study, CDK1 is reported as a synthetic lethality target for KRAS mutation in colon cancer [34]. Our study highlisht RAD51AP1 as a prognostic marker and therapeutic target.…”
Section: Discussionsupporting
confidence: 60%
“…Inhibitors that selectively inhibit CDK4 but not CDK6 (and vice versa) may also be developed, and they could possibly reduce the adverse effects without compromising the therapeutic benefit. Furthermore, CDK2- and CDK1-selective inhibitors will likely be developed, as they may have clinical utility for specific cancer subtypes 55, 6668 …”
Section: Resultsmentioning
confidence: 99%
“…CDK1 was shown to be required for tumour formation and progression. For example, liver-specific ablation of Cdk1 conferred resistance to NRAS G12V -induced liver tumorigenesis 65 , while CDK1 inhibition blocked the growth of KRAS -mutant (G12V, G12D or G12S) colorectal cancer xenografts 66 . However, CDK1 activity is essential for proliferation also in normal, non-transformed cells 59 , arguing against inhibition of CDK1 as a viable therapeutic strategy.…”
Section: Cell Cycle Proteins and Their Role In Physiology And Cancermentioning
confidence: 99%
“…Since our network analysis highlighted shared pathways and complexes across studies, we hypothesized that Network SL genes may represent synthetic lethals that are more robust, and hence more likely to be reproduced in follow up studies. To address this we asked if they were more likely to be recovered in a series of more recent RNAi screens that were not used for network identification as compared to 26 previously published KRAS synthetic lethal genes curated from the literature (Literature SL) (Table 2B) (Costa-Cabral et al, 2016;Kim et al, 2013Kim et al, , 2016. Both Kim et al 2013(Kim et al, 2013 and Kim et al 2016(Kim et al, 2016 studies used panels of KRAS mutant versus wild-type lung cancer lines, and the Costa-Cabral study (Costa-Cabral et al, 2016) used an isogenic panel of colorectal cancer lines.…”
Section: Meta-analysis Of Published Kras Synthetic Lethal Screens Idementioning
confidence: 99%
“…It is as yet undruggable, activates a variety of signaling pathways, and is exemplary to the challenges in identifying synthetic lethals. While a multitude of studies have sought to define KRAS synthetic lethal genes (Costa-Cabral et al, 2016;Kim et al, 2013Kim et al, , 2016Luo et al, 2009;Scholl et al, 2009;Steckel et al, 2012), they have been notable for the fact that they hardly overlap, which has been attributed to the use of different cell lines and screening libraries that may suffer from off-target effects and partial knockdowns (Downward, 2015). As a result, many of the published synthetic lethal genes that have been explored independently have failed to reproduce (Fröhling and Scholl, 2011;Tessema et al, 2014).…”
Section: Introductionmentioning
confidence: 99%